Consumers in a social network: the perception of clothing quality per gender - Freire Castelo, José Sarto; Cabral, José Ednilson de Oliveira (Review of Business Management, 2017)
Purpose – The general objective of this paper is to evaluate the determinant attributes of the perception of clothing quality by the users of a social network and to verify if there are any differences of evaluation of these determinants between genders. Design/methodology/approach – To achieve the objective, a survey was conducted with a sample of 295 consumers. All participants, regardless of gender, were asked to access the SurveyMonkey site link and to answer the questions regarding the quality of clothing for both men and women. Data analysis was performed using descriptive statistics and variance analysis (ANOVA). Findings – The main results show that: 1. The consumers of garments regard as highly important to take into consideration quality attributes when deciding to buy clothes, especially for women in relation to menswear; 2. Women has a higher perception than men as for the evaluation of the quality attributes of both women’s wear and menswear; and, 3. Clothing consumers, in particular consumers of women’s products, only consider to purchase such products if they have, in particular, style, fabric quality and fair price. Originality/value – This research filled in some theoretical and methodological gaps with regard to giving emphasis to gender differences in clothing quality assessment. This is in line with the conclusions of quality research conducted long ago, such as Olson & Jacoby’s (1972), which findings are specific to the type of product and/or consumer investigated. Therefore, generalizations beyond the product or the consumers examined are of dubious validity.